THE MAIN MODERN DISTANCE LEARNING ISSUES - Shoyimkulova Mahzuna Shavkatovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
As today Uzbekistan is making a lot of reforms in education system, especially in teaching foreign languages with new technologies, it is actual to study every new sphere and method of new system. The article learns four characteristics distinguish distance learning and problems.